Daily Inclusion of Potatoes Into a Dietary Guidelines for Americans-Based Dietary Pattern Does Not Adversely Impact Cardiometabolic Risk in Adults With Metabolic Syndrome. (7th June 2021) - Cao, Sisi; Quarles, William; Shaw, Emily; Sasaki, Geoffrey; Dey, Priyankar; Hodges, Joanna; Pokala, Avinash; Bruno, Richard
Abstract: Objectives: Observational studies suggest that the regular ingestion of potatoes adversely affects cardiometabolic health, but controlled studies in humans are needed to establish causality. Our objective was to assess whether daily inclusion of non-fried potato foods as part of a Dietary Guidelines for Americans (DGA)-based dietary pattern would impair cardiometabolic health in adults with metabolic syndrome (MetS). Methods: In a 2-arm, randomized controlled, crossover trial separated by a 2-wk washout period, MetS adults were provided a eucaloric DGA-based dietary pattern containing potato (350 g with 17.5 g/d resistant starch; POTATO) or an energy-matched bagel (0 g/d resistant starch; CON) for 14 d. Fasting blood was collected on d 0 and 14. On d 14, after a 75 g oral glucose tolerance test, brachial artery flow-mediated dilation (FMD) was measured and blood was collected at 30 min intervals for 2 h to assess vascular endothelial function and metabolic excursions, respectively. Circulating endotoxin, glucose, insulin, and nitric oxide metabolites (NOx) were assessed by spectrophotometry, and malondialdehyde (MDA) and arginine and its metabolites by HPLC. Data were analyzed using two-way repeated measures ANOVA. Results: MetS adults ( n  = 27; 32.5 ± 1.3 y; 35.0 ± 1.0 kg/m 2 ) completed the study with no adverse effects or significant changes in body weight. The 14-d DGA-based dietary pattern had a small but significant effect to decrease glucose (107 ± 1.9 vs. 102 ± 1.7 mg/dL; P  = 0.04) and insulin (19 ± 2.9 vs. 14 ± 1.5 μIU/mL; P  = 0.03), but these were unaffected by POTATO. Fasting endotoxin, NOx, and MDA and FMD were also unaffected by POTATO compared to CON, as were postprandial AUC0–2h  of FMD, insulin, glucose, arginine, MDA, endotoxin, and NOx. Conclusions: Findings of this acute controlled trial, which require long-term validation, support that a DGA-based dietary pattern may help to improve insulin resistance and that potatoes can be effectively incorporated into the diet without compromising vascular endothelial function or cardiometabolic health in persons with MetS. Funding Sources: Alliance for Potato Research and Education.